(untitled) (Fiep Bulletin - online, 2015)
At least 141 specialists coming from 22 countries took part in this Siminar which the FIEP – Bulletin announced in its Nos. ans 2, 1967: Germany (24), England (8), Austria (3), Belgium (11) Canada (3), Denmark (2) USA (10), Finland (1), France (3), Holland (2), Hungary(3), Israel (2), Italy (2), Japan (3), Poland (1), Portugal (1), Rumania (2), Sweden (4), Switzerland (34), Czechoslovakia (7), URSS (2), Yugoslavia (1).